Tele-dentistry in COVID-19 era: A conduit for dental care in uncertain times - Saqib Habib; Madiha Khan; Robia Ghafoor (Journal of the Pakistan Medical Association, 2024)
Tele-dentistry encompasses all sorts of digital technologies that involve the exchange of patient’s clinical data from a distant site for the provision of dental health care. Tele-dentistry has emerged from the concept of telemedicine, which has been in practice since the 19th century. In recent times, an upsurge in the digital technologies was noted, which has made the possibility of remote access to dental care. The outbreak of COVID- 19 pandemic has restricted the normal routine ways of clinical practice. In these challenging times, tele-dentistry serves as effective platform for providing dental health care. Tele-dentistry has vast applications across various disciplines of dentistry, including preventive dentistry, paediatric dentistry, oral medicine, and oral pathology etc. Continue...